1976
DOI: 10.1093/geronj/31.2.155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on Creatinine Clearance in Men: A Cross-sectional and Longitudinal Study

Abstract: Standard true 24-hour creatinine clearance determinations were performed on 884 subjects of the Baltimore Longitudinal Study. On the basis of clinical data, subjects were placed in categories indicating the presence of specific diseases or medications which might alter glomerular filtration rate. Subjects not included in these categories were considered normal (N=548). In the normals, cross-sectional analysis by 10-year age groups showed a progressive linear decline in clearance from 140 ml/min/1.73m2 at age 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
371
4
19

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,053 publications
(420 citation statements)
references
References 0 publications
26
371
4
19
Order By: Relevance
“…Early studies by the group of Dr. Nathan Shock in Baltimore strongly supported this thesis. In so-called healthy human volunteers, the cardiac output (Brandfonbrener et al 1955), renal creatinine clearance (Rowe et al 1976) and all other physiological parameters examined were demonstrated to steadily decline with age. However, later by the same group in Baltimore, in a longitudinal study, neither the cardiac output (Rodeheffer et al 1984) nor renal creatinine clearance (Lindeman et al 1985) was shown to decline with age.…”
Section: What Really Declines With Age?mentioning
confidence: 99%
“…Early studies by the group of Dr. Nathan Shock in Baltimore strongly supported this thesis. In so-called healthy human volunteers, the cardiac output (Brandfonbrener et al 1955), renal creatinine clearance (Rowe et al 1976) and all other physiological parameters examined were demonstrated to steadily decline with age. However, later by the same group in Baltimore, in a longitudinal study, neither the cardiac output (Rodeheffer et al 1984) nor renal creatinine clearance (Lindeman et al 1985) was shown to decline with age.…”
Section: What Really Declines With Age?mentioning
confidence: 99%
“…FG menor que 60mL/min/1,73m 2 representa diminuição de cerca de 50% da função renal normal e, abaixo deste nível, aumenta a prevalência das complicações da DRC. [6][7][8] Embora a diminuição da FG relacionada à idade possa dever-se ao processo de envelhecimento normal, a diminuição da FG no idoso é um preditor independente de evolução adversa da doença, tal como óbito e doença cardiovascular. [9][10][11] Além do mais, a FG diminuída no idoso deve implicar em ajustes nas dosagens das medicações, semelhantemente ao que se faz em todos os pacientes com DRC.…”
Section: Diagnóstico Da Drc Avaliação Da Filtração Glomerularunclassified
“…An important age-dependent decrease in the rate of elimination of many drugs is due to the decay in renal function (Rowe et al, 1976). In the elderly the total body water, and the lean body mass, is proportionally smaller and they have a higher proportion of body fat (Crooks et al, 1976).…”
Section: Introductionmentioning
confidence: 99%